Kewenangan Badan Penanggulangan Bencana Daerah Kota Serang Dalam Perlindungan Hukum Bagi Korban Bencana Alam - Ilmi, Nurhasanatul; Ikomatussuniah, Ikomatussuniah; Nurikah , Nurikah (Equality : Jurnal Hukum dan Keadilan, 2025)
Legal protection provided by the Regional Disaster Management Agency is not given equally in receiving assistance in terms of logistical assistance and infrastructure repair. Article 8 paragraph (1) of Serang City Regional Regulation Number 16 of 2011 concerning Disaster Management, BPBD is responsible for disaster management. The problem identification of this research is how the implementation of the authority of the BPBD of Serang City in efforts to protect the law for victims of natural disasters through post-disaster rehabilitation and reconstruction and how the obstacles to the implementation of the BPBD's authority in efforts to protect the law for victims of natural disasters through post-disaster rehabilitation and reconstruction. The theory of this research is the theory of authority and the theory of legal protection. This research uses empirical juridical research methods with qualitative data analysis. The results showed that Disaster Management by BPBD has not been carried out optimally due to the inequality of receiving assistance in logistics and infrastructure assistance. The National Disaster Management Agency provides mandated authority to BPBD based on Serang City Regional Regulation Number 16 of 2011 concerning Disaster Management. Legal protection provided by the Regional Disaster Management Agency is not given equally in receiving assistance in terms of logistical assistance and repair Preventive legal protection by BPBD is provided through prevention such as conducting disaster-related socialization, disseminating disaster information and implementation, enforcing regional spatial plans through the PERKIM Office related to development and repressive legal protection by handling rehabilitation, namely logistical assistance and reconstruction, namely rebuilding facilities and infrastructure. The obstacles are lack of participation from related agencies, overlapping administration, lack of information and understanding of the community, and budget limitations. This research shows that the implementation of post-disaster rehabilitation and reconstruction by BPBD is not given equally to the provision of logistical assistance and infrastructure.